The Future of Open Streets, New York City - Aarti Mehta (International Journal of Urban Design and Development, 2024)
The COVID-19 pandemic necessitated rapid adjustments to New York City public spaces, leading to the implementation of the Open Streets program by the NYC Department of Transportation (DOT). This program transformed streets across the city into pedestrian- friendly zones by limiting vehicular traffic and providing much-needed outdoor space for residents to walk, bike, and socialize safely. While successful in some areas, the program faced significant challenges. These included equity issues, insufficient connectivity, inadequate length and operating hours of Open Streets, and poor maintenance and management. Open Streets were initially unequally distributed, benefiting wealthier, predominantly white neighbor hoods more than others. Furthermore, many Open Streets lacked continuous networks, were too short, and were not operational for enough hours, diminishing their potential impact. Maintenance issues, such as ineffective barriers and signage, often led to drivers' non-compliance, compromising pedestrian safety. To improve the program, the report recommends transitioning successful Open Streets into permanent redesigns under DOT's established programs, expanding the program to more areas, and addressing equity and maintenance issues. The DOT should invest in robust barriers, prioritize quality over quantity in Open Street designations, and extend the length of Open Streets to create a cohesive network. Funding for community groups managing Open Streets is also crucial to ensure their sustainability and success. The report highlights case studies including University Place, Avenue B, Restaurant Row, Broadway, Pearl Street, and Pleasant Avenue, illustrating potential redesigns that could enhance pedestrian and cyclist experiences. The future of Open Streets lies in learning from the initial rollout, addressing its shortcomings, and leveraging community partnerships to create vibrant, safe, and equitable public spaces for all New Yorkers.
Keywords: COVID-19 pandemic; Equity; New York City; Open Streets program; Pedestrianization; Public spaces; Street redesign; community engagement